Role and Possible Mechanisms of Sirt1 in Depression - Guofang Lu (Oxidative Medicine and Cellular Longevity, 2018)
Depression is a common, devastating illness. Due to complicated causes and limited treatments, depression is still a major problem that plagues the world. Silent information regulator 1 (Sirt1) is a deacetylase at the consumption of NAD+ and is involved in gene silencing, cell cycle, fat and glucose metabolism, cellular oxidative stress, and senescence. Sirt1 has now become a critical therapeutic target for a number of diseases. Recently, a genetic study has received considerable attention for depression and found that Sirt1 is a potential gene target. In this short review article, we attempt to present an up-to-date knowledge of depression and Sirt1 of the sirtuin family, describe the different effects of Sirt1 on depression, and further discuss possible mechanisms of Sirt1 including glial activation, neurogenesis, circadian control, and potential signaling molecules. Thus, it will open a new avenue for clinical treatment of depression.